Breast Cancer During Pregnancy: A Marked Propensity to Triple-Negative Phenotype - Allouch, Soumaya; Gupta, Ishita; Malik, Shaza; Al Farsi, Halema F.; Vranic, Semir; Al Moustafa, Ala-Eddin (Frontiers in Oncology, 2020)
Breast and cervical cancers comprise 50% of all cancers during pregnancy. In particular, gestational breast cancer is considered one of the most aggressive types of cancers, which is a rare but fatal disease. However, the incidence of this type of cancer is increasing over the years and its prevalence is expected to rise further as more women delay childbearing. Breast cancer occurring after pregnancy is generally triple-negative with specific characterizations of a poorer prognosis and outcome. On the other hand, it has been pointed out that this cancer is associated with a specific group of genes that can be used as precise targets to manage this deadly disease. Indeed, combination therapies consisting of gene-based agents with other cancer therapeutics is presently under consideration. We herein review recent progress in understanding the development of breast cancer during pregnancy and their unique subtype of triple-negative which is the hallmark of this type of breast cancer.